Improper Disposal Of Hazardous Waste And Its Impact On Human Health: In Special Reference To India - Vivekanand, Vivekanand; Grewal, Upendra (Journal of Neonatal Surgery, 2025)
India is a developing country which is moving ahead on the path of development with its diversity. One of the biggest challenges facing this rapidly growing Indian economy is the production of hazardous waste materials. Processing hazardous waste materials has become the biggest problem for all developed and developing countries. Because it not only affects environment but is also causing serious damage to the human health. Due to which natural The effect of continuous use of these substances is also clearly visible on human health. The objective of this study is to comprehend the impact of hazardous waste on human health and to deal with problems associated with it. The results revealed that hazardous waste, when incorrectly treated, processed and disposed of, has a significant impact on public health and the environment. The most severe consequences of insufficient waste management are air pollution, water supply depletion, and the spread of human diseases. Cities become untidy and dirty, have a negative impact on people's health, harm flora and fauna, and hinder the economy of countries. Some of the prevention such as hazardous waste handling, dilution, a tube-well structure using well-logging methods and other forms of geophysical monitoring designed specifically for the contaminated area, as well as the different treatment systems, could also be advised.